An objective study of behavior of permanent magnet synchronous motor under abnormal conditions - H. Al-Tameemi, Zaid; H. Enawi, Hayder; M. Al-Anbary, Karrar; H. Al-Mamoori, Dalya; M. Almukhtar, Hussam (International Journal of Engineering and Technology, 2018)
Permanent magnet synchronous motors (PMSM) can be used directly in place of the induction motors (I.M) for several industrial applications since it is characterized by high efficiency, high power factor, and high power compared to I.M. However, this type of motor suffers from some abnormal conditions that result in minimizing power quality such as voltage sags, temporary disturbances, and faults within the network. In this paper, the behavior of PMSM has been studied under the above conditions in a Matlab/Simulink environment. It was noticed that such problems caused an increase in the amount of torque and current in this motor which impacted negatively on the motor speed and influenced the behavior of PMSM.Â